2017
DOI: 10.1080/14737140.2017.1348232
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in targeted advanced lung cancer therapy in the elderly

Abstract: With increasing life expectancy over the last several decades, the incidence of lung cancer is increasing in the elderly population too. In clinical practice about 50% of lung cancers were diagnosed in patients older than 65 years and about 30-40% of lung cancer patients are 70 years old or more. Treatment of elderly patients with non-small-cell lung cancer (NSCLC) represents a challenge in clinical practice, because these patients are not eligible for aggressive therapies for the age-related reduction of func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 89 publications
0
11
0
1
Order By: Relevance
“…11 The recent head-to-head randomized trials, LUX-Lung 7 (LL7), 12 ARCHER-1050, 15 and FLAURA 16 have shown that afatinib, dacomitinib, and osimertinib are more active than first-generation EGFR TKIs in a first-line setting. Although data from small early-phase studies, retrospective analyses, and subgroup analyses suggest that all approved, and emerging, EGFR TKIs might be similarly effective and well tolerated in older and younger populations, 17,18 there have been no prospective phase III trials specifically conducted in elderly patients (ie, 65 years or older) in this setting to help drive therapeutic decisions in this subset of patients. 5,19 To evaluate the effect of advancing age on clinical outcomes and tolerability with first-line afatinib in patients with EGFRm þ NSCLC, preplanned subgroup analyses of patients aged years and older and younger than 65 years in LL3 and LL6 were conducted.…”
Section: Introductionmentioning
confidence: 99%
“…11 The recent head-to-head randomized trials, LUX-Lung 7 (LL7), 12 ARCHER-1050, 15 and FLAURA 16 have shown that afatinib, dacomitinib, and osimertinib are more active than first-generation EGFR TKIs in a first-line setting. Although data from small early-phase studies, retrospective analyses, and subgroup analyses suggest that all approved, and emerging, EGFR TKIs might be similarly effective and well tolerated in older and younger populations, 17,18 there have been no prospective phase III trials specifically conducted in elderly patients (ie, 65 years or older) in this setting to help drive therapeutic decisions in this subset of patients. 5,19 To evaluate the effect of advancing age on clinical outcomes and tolerability with first-line afatinib in patients with EGFRm þ NSCLC, preplanned subgroup analyses of patients aged years and older and younger than 65 years in LL3 and LL6 were conducted.…”
Section: Introductionmentioning
confidence: 99%
“…There are concerns regarding aggressive therapies causing excessive toxicity in an older cohort, elderly patients themselves choosing less aggressive therapy, and the usefulness of therapy in patients with worsening performance status and medical comorbidities. 7,8,[18][19][20][21] Given these concerns regarding aggressive chemoradiation in an elderly population, targeted agents and immunotherapy also play a role in therapy. Although typically reserved for patients with metastatic disease, recent reports have indicated that the incidence of molecular mutations appears congruent between patients with early-stage and late-stage disease.…”
Section: Discussionmentioning
confidence: 99%
“…Втім, слід зазначити, що НДРЛ, загалом, дуже поширений серед осіб похилого віку. Зокрема, близько 50% випадків раку легені діагностується у людей старше 65 років, та близько 30-40% -у осіб старше 70 років [33].…”
Section: обговоренняunclassified